Experimental characterization of Mode I fatigue delamination growth onset in composite joints: A comparative study - Francis Mariana González Ramírez; Felipe Parise Garpelli; Rita de Cássia Mendonça Sales; Geraldo Maurício Cândido; Mariano Andrés Arbelo; Marcos Yutaka Shiino; Maurício Vicente Donadon (Materials & Design, 2018)
This work focuses on Mode I fatigue induced delamination growth onset characterization of co-cured (CC), co-bonded (CB) and secondary bonded (SB) composite joints with an epoxy interleaf. The CC joints used in this work comprise only fibers and resin, while, CB and SB joints contain an adhesive film. Experimental tests were carried out at room temperature using double cantilever beam (DCB) specimens. The delamination behavior was evaluated in terms of the strain energy release rate (SERR) considering a no-growth criterion based on 106 cycles without crack propagation. For Mode I cyclic loading, the threshold values of the CB and SB joints were about 2.5 times higher than the one achieved by the CC joints, presenting a better performance in terms of fatigue delamination growth-onset. A fractographic study was conducted using scanning electron microscopy in order to relate the SERR results with the joint′s failure mechanisms. It was observed that there is a good mechanical compatibility between the substrate and adhesive in the CB and SB joints studied herein. The results found in this paper indicated that the Mode I SERR threshold values were not significantly affected by the interleaf. Keywords: Mode I fatigue delamination, Bonding methods, Double cantilever beam specimens, Strain energy release rate, Fatigue delamination growth onset